Konsep Manajemen Kelas - Rosandi, Asep; Fauzan, Muhamad Dwi; Rahmadan, Riski; Wiranto (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
Classroom management is an aspect of education that is often the main concern of prospective teachers, new teachers, and even experienced teachers. Because prospective teachers, new teachers, and experienced teachers want students to learn optimally. In the sense that the teacher is able to convey the lesson material and can be received by students well. One of the characteristics of a professional teacher is a teacher who is able to manage classes well. The creation of a comfortable classroom is a study of classroom management. Because classroom management is a series of teacher behaviors in an effort to create and maintain classroom conditions that allow students to learn well. In the classroom all aspects of learning meet and process, teachers with all their abilities, students with all their backgrounds and potentials, curriculum with all its components, methods with all its approaches, media with all its tools, materials with all its learning resources meet and interact in the classroom. The method that the author uses is a method of approaching literacy studies which takes from reference materials for journal books and others Keywords: teachers; management; class